ANALISIS PENGELOLAAN ASET TETAP BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 19 TAHUN 2016 (STUDI PADA PEMERINTAH KABUPATEN ALOR PROVINSI NUSA TENGGARA TIMUR) - Seliamang, Yunelci Martha; Tapatfeto, Dessy; Pasmiati, Putu (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
The Alor Regency Government received an Unqualified Opinion for its 2021 Financial Statements, but there are some noteworthy issues, namely asset management, which requires greater attention. The purpose of this study is to determine the implementation of Regional Property/Fixed Asset management in the Alor Regency Government, East Nusa Tenggara, and the results of the fixed asset management inventory administration. This study will ultimately provide results on whether fixed asset management in the Alor Regency Government, NTT, complies with Minister of Home Affairs Regulation No. 19 of 2016 concerning Regional Property Management. This will benefit the Property Manager (BPAD Alor Regency) in maintaining an Unqualified Opinion (WTP). This study employed a descriptive-qualitative approach. Data collection included observation, interviews, literature review, documentation, and internet searches. Data collection in this study was conducted through a review of existing literature.